Recebe o evangelho de Cristo do qual foste constituído mensageiro: a missão do diácono permanente como servidor da mesa da palavra - Bendinelli, Julio Cesar (2009)
The mission of the permanent deacon as Server of the table of the Word and his contribution to the current missionary demand of the Roman Catholic Church in the field of Evangelization. The investigation, which stems from texts written by the II Vatican Council and reaches to post-council magisterial documents, has as its goal to value the exercise of the munus docendi ecclesiae conferred to the permanent deacon upon his sacramental ordination. It is based on bibliographical research of the sources cited in the references and is presented in three chapters. The first chapter deals with the ministry of the permanent deacon as reinstated by the II Vatican Council. It examines the similarities and differences between the ordained and non-ordained ministries in the Roman Catholic Church. It verifies the functions conferred by ordination in the areas of the Word, of liturgy and of charity. It investigates elements of service to preaching since the origin of diaconal ministry in the New Testament and presents the essence of the ministry of the ancient deacons. The second chapter is dedicated to the service of the permanent deacon to the table of the Word of God. It investigates the practical meaning of the council s recovery of the notion of the union of the two tables Word and Eucharist, with the consequent revalorization of the place of the Word of God in the liturgy and in the life of the Catholic faithful. It seeks the presence of the expression Bread of the Word of God in the ecclesial Tradition. It investigates the diaconal ministry of the Word in the postcouncil ecclesial Magisterium and in the documents of the Vatican Congregations, of the CNBB and of CELAM. It analyzes the elements of the rite of diaconal ordination and its implications for the mission with which the deacon is invested in the Catholic Church. The third chapter proposes ways in which the permanent deacon can contribute in the field of Evangelization, interpreting the results of the preceding investigations from the prior chapters. It presents the pastoral reality of the diaconal ministry in the Church and suggests a sustainable and at the same time relevant place for the permanent deacon. It presents the diaconate in the context of the ordained ministry based on what the author calls a symbolic key . It puts forth a general summary of what was brought up in the research with regards to the functions in the sphere of evangelization and the preaching of the Word that are of the competence of the permanent deacon. It selects four areas where the diaconal ministry can collaborate in the current missionary demand of the Church: renewed catechesis, evangelization of the families and small communities, ecumenism and the public dimension of the Church. It concludes that the diaconal role in the field of evangelism has not been well used, encouraged or valued in the Church and in society. Being thus, the deacons should assume their share of the service that behooves them as messengers of the Word, since, there are certainly more tasks in the areas of preaching and teaching than they currently carry out, since all that refers to the preaching of the Gospel, to catechesis, to spreading the Bible and its explanation to the people was ordinarily conferred upon them